2011
DOI: 10.1002/chem.201101595
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap to Implementing Metal–Organic Frameworks in Electronic Devices: Challenges and Critical Directions

Abstract: Metal-organic frameworks (MOFs) and related material classes are attracting considerable attention for applications such as gas storage, separations, and catalysis. In contrast, research focused on potential uses in electronic devices is in its infancy. Several sensing concepts in which the tailorable chemistry of MOFs is used to enhance sensitivity or provide chemical specificity have been demonstrated, but in only a few cases are MOFs an integral part of an actual device. The synthesis of a few electrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
352
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(353 citation statements)
references
References 193 publications
1
352
0
Order By: Relevance
“…With the number of reports on conductive MOFs rapidly increasing, a roadmap for future progress is illustrated in Figure 4, drawing from the earlier perspective of Allendorf et al 46 .…”
Section: Discussionmentioning
confidence: 99%
“…With the number of reports on conductive MOFs rapidly increasing, a roadmap for future progress is illustrated in Figure 4, drawing from the earlier perspective of Allendorf et al 46 .…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of their modular open framework architecture [3], MOFs feature large surface areas typically in the range of 1000 to 10 000 m 2 g −1 [1], which are far superior to any traditional porous materials, such as inorganic zeolites and activated carbons. In addition to familiar uses of porous materials, where MOFs have extensively been targeted at gas storage [4] and carbon dioxide capture [5], trends have recently shifted towards less conventional applications, ranging from microelectronics and dielectrics to photocatalysis for sustainable hydrogen production, and from drug encapsulation to multifunctional sensors [6]. Realization of these emergent technologies requires knowledge of their fundamental physical properties, particularly an understanding of the lattice dynamics [7] underpinning the elasticity of MOFs [8,9], which is central to structural stability [10] and thermo-mechanical behavior of framework materials [11].…”
mentioning
confidence: 99%
“…MOFs are porous materials comprised organic ligands coordinated to transition metal ions [9,10]. Recently, research surrounding the chemistry and diverse applications of MOF-based materials has experienced tremendous growth [11][12][13][14]. For instance, Proietti et al demonstrated that the addition of iron precursors with a Zn-ZIF can give superior fuel cell performance [15].…”
Section: Introductionmentioning
confidence: 99%